(untitled) (International Journal of Biomedical and Advance Research, 2019)
Background: The papulosquamous skin disorders are a heterogenous group of disorders, showing overlap in morphology and distribution of lesions that leads to difficulty in diagnosis. Hence the present study was undertaken to record the frequency and to study pattern of clinical and histopathological features of papulosquamous lesions of skin with clinicopathological correlation. Method: Total 125 cases clinically diagnosed as papulosquamous lesions of the skin, before starting the treatment and on attending the outdoor skin department were enrolled and studied in the Department of Pathology at Grant Government Medical College, Mumbai over a period of 2 years from June 2015 to May 2017. Results: Papulosquamous lesions of the skin constituted 14.74% of the total number of skin biopsies. Majority of patients were in the age group of 21–30 years (26.4%) with male preponderance (62.4%). Histopathologically, lichen planus was the most common lesion (54.4%) followed by psoriatic lesions (24.8%), pityriasis rubrapilaris (5.6%) and parapsoriasis (3.2%). Clinicopathological correlation was positive in 87.2% cases and negative in 12.8% cases. Conclusion: Histopathology serves as a diagnostic tool and rules out other lesions which mimic papulosquamous disorders. Histological features of some disorders (psoriasis and lichen planus) are quite diagnostic, while few disorders (lichen striatus and pityriasis rosea) may show some overlap. In these circumstances an attempt at clinicohistopathological correlation serves as an ideal approach. Thus, distinct histopathological features and clinicohistopathological correlation gives a conclusive diagnosis.